Pragmatic Interoperability in IoT: A Systematic Mapping Study - Muniz, Matheus H.S.; David, José Maria N.; Braga, Regina; Campos, Fernanda; Ströele, Victor (Proceedings of the Brazilian Symposium on Multimedia and the Web (WebMedia); 2019: Proceedings of the 25th Brazilian Symposium on Multimedia and the Web, 2019)
The Internet of Things (IoT) is a technological paradigm which aims to connect, in a global network, several devices and intelligent machines capable of exchanging information with each other. IoT purpose will only be achieved when the entities present in this network can fully interoperate with each other. However, the heterogeneity of devices, and the contexts in which they are inserted, can create obstacles in terms of interoperability. This paper aims to describe a systematic mapping carried out with the aim of identifying primary studies dealing with interoperability in IoT context. The focus was on the pragmatic interoperability level, since most researches of the works propose solutions to support the technical and semantic interoperability levels. Twelve papers were selected and analyzed aimed of answering the research questions formulated. Few of them addressed pragmatic interoperability support and have explored solutions in the context of IoT.